Population pharmacokinetics of plasma‐derived factor IX: procedures for dose individualization. (23rd February 2016) - Brekkan, A.; Berntorp, E.; Jensen, K.; Nielsen, E. I.; Jönsson, S.
Abstract : Essentials A population pharmacokinetic model and sparse factor IX (FIX) levels may be used in dose individualization. FIX sampling schedules for dose individualization were explored and compared with fixed doses. Individual FIX doses were acceptably predicted with only two samples drawn post dose (days 2 and 3). Pharmacokinetic dose individualization resulted in better target attainment than a fixed‐dose regimen. Summary: Background: Population pharmacokinetic (POPPK) models describing factor IX (FIX) activity levels in plasma, in combination with individual FIX measurements, may be used to individualize dosing in the treatment of hemophilia B. Objectives: The aim was to reevaluate a previously developed POPPK model for FIX activity and to explore the number and timing of FIX samples required in pharmacokinetic (PK) dose individualization. Methods: The POPPK model was reevaluated using an extended data set. Several sampling schedules, varying with respect to the timing and number of samples, were evaluated in a simulation study with relative dose errors compared between schedules. The performance of individually calculated doses was compared with commonly prescribed FIX doses with respect to the number of patients with a trough FIX activity > 0.01 U mL −1 . Results and conclusions: A three‐compartment PK model best described the FIX activity levels. The number and timing of samples greatly influenced imprecision in dose prediction. Schedules with single samples taken on both day 2 and day 3 were identified as being convenient schedules with an acceptable performance level. Individually calculated doses performed better with respect to patient target attainment than a fixed 40 U kg −1 dose regardless of how many samples were available to calculate individual doses. The results of this study suggest that PK dose tailoring with limited sampling may be applicable for plasma‐derived FIX products.